Effect of Constant Temperature on Development and Reproduction of the Cotton Aphid (Aphis gossypii) (Glover) (Hemiptera: Aphididae) on Gossypium hirsutum in Laboratory Conditions - 2Wadikar M.S.3, 1Tawar D.S.1; 1Muley S.P.2, Nimbalkar R.K.1*, 1Shinde S.S.2, (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US;">Temperature-dependent development, survivorship and reproduction of the cotton aphid, Aphis gossypii on Gossypium hirsutum were evaluated at six constant temperatures (100, 150, 200, 250, 300 and 350C). The clean statistical breaks between developmental durations of all immature stages of aphids held at 100 and 150C indicate that at lower temperatures, all immature aphid stages (1st to 4th instars) are affected similarly by temperature changes. In viewing the survivorship curves (lx) for aphids held at the six constant temperatures, a general trend is evident. As temperature increased, survivorship progressively fell more precipitously, indicating increasing aphid mortality at a younger age. At 100, 150, 200, 250, 300 and 350C, aphid survivorship dropped below 80% at 39, 29, 33, 21, 20, and 14 days of life, respectively. Gross reproductive rate (GRR) an indicator of lifetime fecundity, ranged from 9.8 for aphids held at 100C to 58.9 for aphids held at 300C. A general rise in GRR was observed with rising temperature to 300C. The optimum temperature is closer to 250C. The results of this study agree with previous studies that the optimum aphid development temperature (held constant) in a laboratory study is 250 to 300C.